Assessment of the adaptogenic properties of herbal tea based on pine needles and microstrobiles - S. D. Zhamsaranova; V. G. Shiretorova; S. A. Erdyneeva; A. A. Tykheev; S. N. Lebedeva (Пищевые системы, 2025)
The scientific community shows an increasing interest to plant antioxidants as a means of alimentary restoration of functional reserves of the body after physical and emotional stresses. The aim of the work was to assess the adaptogenic activity of herbal tea developed on the basis of by-products of pine growing on the territory of Buryatia. The object of the research was a plant composition (herbal tea) consisted of tea leaves, sea-buckthorn press cake, pine microstrobiles and needles. Adaptogenic properties of herbal tea were studied on the model of immunosuppression caused by the cytostatic drug azathioprine administered to experimental animals every day orally. Behavioral reactions of animals were assessed in the open field test; the general physical endurance in the forced swim test with weight load. Histomorphological analysis of the organs was carried out using the standard methods. In the state of immunosuppression caused by azathioprine, the exploratory activity and physical endurance of animals decreased, anxiety increased, the relative weight of immune organs (thymus and spleen) decreased and the relative weight of the organ that detoxifies xenobiotics, liver, increased. Morphometric studies showed that after administration of azathioprine significant morphofunctional changes were observed in the thymus and spleen of mice, which suggested a decreased functional activity of the organs. A decrease in the number and size of thymic Hassal’s bodies and a reduction of nucleated cells were observed in the thymus, while a significant two-fold decrease in the average area of follicles and a decrease in thickness of germinal centers were noticed in the spleen compared to those in the intact group. Introduction of herbal tea upon administration of azathioprine make it possible to alleviate its negative effect; with that, some indicators of the structures of the thymus and spleen corresponded to the values of the intact group. The summary content of antioxidants in herbal tea was 430.48 mg / 100 ml. Restoration of the non-specific reactivity of the body of the experimental animals subjected to immunosuppression apparently is linked with the antioxidant activity of the biologically active substances in the composition of herbal tea.